PENGARUH KEMAMPUAN MEMBACA PEMAHAMAN DAN MINAT BACA TERHADAP HASIL BELAJAR BAHASA INDONESIA PESERTA DIDIK KELAS IV SDN SAMPOJA - Nurzahrawani Zakiyah; Ida Ermiana; Darmiany (STKIP Subang, 2025)
This study aims to examine the effect of reading comprehension ability and reading interest on Indonesian language learning outcomes of fourth-grade students at SDN Sampoja. The research employed a quantitative approach with a correlational design. The population consisted of all fourth-grade students, with a total sample of 30 students selected using a total sampling technique. Data were collected through a reading comprehension test, a reading interest questionnaire, and an Indonesian language achievement test. Data analysis techniques included descriptive statistics, normality tests, Pearson correlation analysis, simple regression, and multiple regression analysis. The results showed a strong and significant positive correlation between reading comprehension ability and Indonesian language learning outcomes (r = 0.913, p < 0.01). Reading interest also had a positive and significant correlation with learning outcomes (r = 0.767, p < 0.05). Furthermore, reading comprehension ability and reading interest simultaneously had a significant effect on Indonesian language learning outcomes, with a determination coefficient of 84.3%. These findings indicate that improving students’ reading comprehension ability, supported by strong reading interest, plays a crucial role in enhancing Indonesian language learning outcomes at the elementary school level. Keywords: Reading comprehension ability, reading interest, Indonesian language learning outcomes